2022
DOI: 10.1021/acs.orglett.2c02442
|View full text |Cite
|
Sign up to set email alerts
|

[2 + 3] Annulative Coupling of Tetrahydroisoquinolines with Aryliodonio diazo compounds To Access 1,2,4-Triazolo[3,4-a]isoquinolines

Abstract: Base promoted one-pot annulative coupling of 1,2,3,4tetrahydroisoquinolines (THIQs) with hypervalent iodine(III) species aryliodonio diazo compounds has been devised for the direct construction of 1,2,4-triazolo[3,4-a]isoquinoline derivatives at room temperature in open air for the first time. This approach involves [2 + 3] cascade annulation of nucleophilic THIQ with an electrophilic aryliodonio diazo compound via N−H and α-C1(sp 3 )−H difunctionalization of THIQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…[64] In 2022, a series of 1,2,4-triazoles 43, 45 and 47 were obtained from the [2 + 3] cascade annulation of tetrahydroisoquinolines 42 or azaarenes (44 or 46) with diazomethyl-substituted iodine(III) compounds 3 a-c or 3 h (Scheme 15). [65,66] These conversion methods were achieved through nucleophilic reactions to construct C(sp 2 )À N bonds, however the process was not the same. For example, diazomethyl-substituted iodine(III) compound was nucleophilic attacked by tetrahydroisoquinoline or azaarene to generate intermediates A and D, respectively.…”
Section: C(sp 2 )à N Bond-forming Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[64] In 2022, a series of 1,2,4-triazoles 43, 45 and 47 were obtained from the [2 + 3] cascade annulation of tetrahydroisoquinolines 42 or azaarenes (44 or 46) with diazomethyl-substituted iodine(III) compounds 3 a-c or 3 h (Scheme 15). [65,66] These conversion methods were achieved through nucleophilic reactions to construct C(sp 2 )À N bonds, however the process was not the same. For example, diazomethyl-substituted iodine(III) compound was nucleophilic attacked by tetrahydroisoquinoline or azaarene to generate intermediates A and D, respectively.…”
Section: C(sp 2 )à N Bond-forming Reactionsmentioning
confidence: 99%
“…The experimental results showed that various tetrahydroisoquinolines 42 bearing electron-withdrawing and electrondonating aryl groups as well as a methyl group at the alkyl linker afforded the corresponding 1,2,4-triazolo[3,4a]isoquinolines 43 in 62-78 % yields. [65] The [3 + 2]-dipolar cycloaddition between azaarenes (44 or 46) and compounds (3 a or 3) in the presence of Na 2 CO 3 afforded 1,2,4-triazolyl azaarenes 45 and 47 in 37-71 % and up to 69 % yields, respectively. [66] Diazirines containing two nitrogen atoms in ternary heterocycles have been widely used as intermediates for carbene generation and can release nitrogen under appropriate conditions of exposure.…”
Section: C(sp 2 )à N Bond-forming Reactionsmentioning
confidence: 99%
“…Hypervalent iodine reagents are readily available mild oxidants that are considered to be environmentally benign alternatives to metal-based oxidants and are widely used in modern organic synthesis. Their synthetic applications are tremendous and span a wide range of oxidative transformations such as oxidative cyclization/heterocyclization, difunctionalization of alkenes, phenol dearomatization, oxidation of sulfur compounds, , α-functionalization of carbonyl compounds, and molecular rearrangement reactions. , Hence, they are valuable tools in the synthetic organic chemistry toolbox.…”
Section: Introductionmentioning
confidence: 99%
“…The β-ketothioamides possess multiple electrophilic and nucleophilic centers, which can preferably react with their choice of coupling partners in a chemo- or regioselective fashion to produce the corresponding heterocyclic compounds . Our research group is focused on developing a novel platform in organic synthesis using tailored hypervalent iodine reagents as an electrophilic diazo source. , To date, the reaction between β-ketothioamides and α-aryliodonio diazo compounds has not yet been accomplished and remains unexplored. As part of our continuing efforts on β-ketothioamides and α-aryliodonio diazo compounds, a new transition-metal- and base-free approach for the construction of thiazolothiadiazoles has been devised.…”
mentioning
confidence: 99%
“…We recently utilized β-ketothioamides with a different class of α-diazo compounds to construct thiazolidinones, but retaining the nitrogen atoms of the diazo fragments was formidable for the organic chemist (Scheme b) . Very recently, our group utilized α-aryliodonio diazo compounds with commercially available tetrahydroisoquinolines, where we successfully utilized the nitrogen of the diazo fragments for the construction of isoquinoline-fused triazoles (Scheme c) . Hence, we envisioned that by employing same iodanes with β-ketothioamides we might be able to furnish the corresponding heterocycles with an incorporated diazo nitrogen.…”
mentioning
confidence: 99%